Playing catch-up: Investigating public and institutional policies for OER practices in Australia - Carina Bossu; Mark Brown; David Bull (Flexible Learning Association of New Zealand, 2011)
This article explores some of the most well-known Open Educational Resource (OER) initiatives worldwide and then reports on OER developments in Australia. It also discusses a current research project funded by the Australian Learning and Teaching Council (ALTC), including its design and methods of data collection and analysis. Although the study reported here is ongoing, a survey of the tertiary sector to establish the current 'state of play' of OERs in Australia has been completed. The authors examine a preliminary analysis that focuses mostly on OER policies at governmental and institutional levels. The analysis shows that the OER movement remains relatively immature in Australia. Also, according to the survey's participants, the government and educational institutions need to give much greater consideration to a regulatory framework in which the use of OER and Open Educational Practices (OEP) can be fostered and encouraged. Isolated OER activities exist, but there appears to be a great deal of catching up required if Australia is to have coordinated initiatives to foster innovation and a culture of more OEPs.